PENERAPAN EVIDENCE BASED NURSING (EBN) METODESAFETY MORNING TALK DENGAN MANAJEMEN STRES:TERAPI SELF TALK DAN TERAPI TERTAWA DALAMMENGATASI STRES KERJA PERAWAT DI RUANGHEMODIALISA RSUD DR. CHASBULLAH ABDULMADJIDKOTA BEKASI - Anindita Putri Suwarno (2023)
Stress is a response and emotional responses both physically and mentally resulting from a mismatch between self-skills and the demands received. The results of the questionnaire showed that 3 nurses (60%) were in the high stress category and 2 nurses (40%) were in the mild stress category. Based on these results, the authors aim to apply the safety morning talk method with stress management: self talk therapy and laughter therapy. The case study begins by distributing the modified Expanded Nurses Stress Scale (ENSS) questionnaire, after collecting data on nurses' work stress, the authors then implement it in accordance with Evidence Based Nursing (EBN) safety morning talk method with stress management: self talk therapy and laughter therapy . The intervention was carried out for 3 consecutive days with a duration of 10 minutes each session. The results of the posttest showed a decrease in the level of work stress for nurses as much as 7-14 point scores from the pretest and posttest results. The author hopes that nurses can implement the application of evidence based nursing safety morning talk methods with stress management: self talk therapy and laughter therapy in dealing with work stress.